The efficacy and safety of rotavirus vaccines in countries in Africa and Asia with high child mortality. Issue 12 (15th March 2022) - Henschke, N.; Bergman, H.; Hungerford, D.; Cunliffe, N.A.; Grais, R.F.; Kang, G.; Parashar, U.D.; Wang, S.A.; Neuzil, K.M.
Abstract: Rotavirus remains a leading cause of diarrhoeal morbidity and mortality in young children and rotavirus vaccines are critical for reducing global disease burden. This report addresses the performance of rotavirus vaccines in countries with high child mortality. We performed a sensitivity analysis as part of a systematic review on rotavirus vaccines to inform development of World Health Organization vaccine recommendations. The efficacy of four prequalified vaccines against severe rotavirus gastroenteritis was similar across high mortality settings in Asia and Africa. Within the first year following vaccination, vaccine efficacy for the four vaccines ranged from 48% to 57% while in the second year, efficacy ranged from 29% to 54%. The four vaccines showed no increase in intussusception risk in these settings. All four vaccines appear to prevent significant numbers of severe rotavirus gastroenteritis episodes with no measurable increase in intussusception risk in high mortality settings in Africa and Asia.